Functionality of Physical Activity Referral Schemes (PARS): A Systematic Review - Albert, Francis Ali; Crowe, Melissa J.; Malau-Aduli, Aduli E. O.; Malau-Aduli, Bunmi S. (Frontiers in Public Health, 2020)
Abstract Background: Physical activity (PA) is vital to maintaining good health. However, WHO estimates that 60% of the world’s population are inadequately active. To enhance PA, Physical Activity Referral Schemes (PARS) have been established by some countries. Objective: This study examined the functionality of the PARS process across different countries. Methods: This systematic review was performed and reported in accordance with the PRISMA guidelines. Sixteen electronic databases were searched from January 1990 to May 2020. PARS studies, published in English language and in peer-reviewed journals, that reported adherence, outcomes, disease conditions, interventions, facilitators and barriers, were included in this review. Results: Twenty-seven studies conducted across eight countries met the inclusion criteria. Most patients were referred for sedentary/inactivity reasons and supervised group-based activities was the most used intervention. Participants’ average adherence rate was 77.5%. Adherence was either facilitated or hindered by type of support provided during and after intervention period. Inclusion of PA allied health specialist in the intervention enhanced positive health outcomes. Conclusion: PARS is a key driver and motivator for individuals to undertake and adhere to PA interventions. Utilisation of guidelines on evidence-based interventional PA for different types of diseases, effective use of common group supervised activities and the involvement of PA specialists may aid PA adherence and foster positive health outcomes.